Bilateral Femoral Insufficiency Fractures Likely Related to Long-Term Alendronate Therapy - Ravindra Gudena; Jason Werle; Kelly Johnston (Journal of Osteoporosis)
Osteoporosis-related fractures are a major public health problem and one in two women and one in four men are affected with osteoporosis-related fractures. Alendronate (Fosamax) is one of the first bisphosphonates used to treat osteoporosis effectively. Recently, however, there is a concern regarding long bone insufficiency fractures related to long-term alendronate therapy. We report a case of bilateral femoral insufficiency fractures likely related to long-term alendronate therapy, the classic symptoms, signs, and treatment of these fractures.